Critiquing the critique of the paradigm of education for the countryside - Camacho, Rodrigo Simao; Fernandes, Bernardo Mancano [UNESP] (Univ Estadual Sudoeste Bahia, 2017)
This article presents a theoretical debate about the paradigms of the Agrarian Question and the Education for the Countryside, explaining the theoretical processes of construction of different interpretations from the proletarian and peasant strands of the Agrarian Question Paradigm. The discussion between these aspects is analyzed in this article in which we comment on the work of Albuquerque, 2011, that from a mistaken referential does not understand the reality in which the Education for the Countryside paradigm is being constructed. These are orthodox positions that do not contribute to the advancement of Education for the Countryside and for this reason, must be answered. During the twenty years of Education for the Countryside, the Orthodox criticisms produced since the Agrarian Question paradigm are minimal, but we consider them important in the theoretical debate. Even to show their fallacies and their decadence in the academy and movements, in which the postulants of orthodox positions are inexpressive. This is not a controversial article, it is a strong article that demarcates a theoretical position in a critical posture to the critique of the Education for the Countryside paradigm.
Keywords: Paradigmatic debate; Education for the countryside; Agrarian question paradigm